IMPLEMENTASI9NILAI-NILAI ASWAJA PADA9PEMBELAJARAN PAI SISWA KELAS9VII SMP PLUS9HIDAYATUL MUBTADIIN SINGOSARI - M Nidhomuddin; Azhar Haq; Adi Sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The teachings of Islam Ahlussunnah9Wal Jamaah9abbreviated as ASWAJA are considered in9accordance with0Indonesian Islam. Because0in it there are the0principles or values of.Tawassuth,9Tawazun,9Tasamuh9and I'tidal and9Amar Ma'ruf Nahi9Munkar (calling for goodness to stay away from prohibitions). The focus of the research is 1) How are Aswaja values implemented in PAI learning for seventh grade students of SMP Plus Hidayatul Mubtadiin Singosari? 2) What are the obstacles faced in implementing Aswaja values in PAI learning for seventh grade students of SMP Plus Hidayatul Mubtadiin Singosari?. The0research approach is0qualitative research, with the0type of descriptive research. Data collection9techniques are participantnobservation, in-depth interviews9and documentation. The analysis0technique used is0data reduction, data0presentation and conclusion0drawing. The conclusion is that the0implementation of Aswaja values in0PAI learning for class VII SMP Plus Hidayatul Mubtadiin Singosari is carried out using several methods. The Aswaja values in question are the values of Tasamuh (tolerance), Tawasuth (moderate),9I'tidal (fair), Amar ma'ruf9Nahi Munkar and Tawazun0(balanced). The implementation of these values is used by several methods, including: a) Understanding Method, b) Habituation Method, c) exemplary method (Uswatun Khasanah). The0obstacles faced in the0implementation of Aswaja values in0PAI Learning class VII SMP Plus Hidayatul Mubtadiin Singosari include: a) socializing outside school, b) lack of communication with parents, c) lack of motivation in learning.